Juridical Review Of Nominee Agreement In Land Of Tenure Property Rights Under The Book Of Civil Law And Agraria - Indah Esti Cahyani; Aryani Witasari; M Farid Amirullah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Nominee agreement is an agreement made between someone who by law can not be the subject of rights to certain lands (property rights), in this case that foreigners (WNA) and Indonesian Citizen (citizen), with the intention that the foreigners can master land de facto property rights, but legal-formal (de jure) land property rights are assigned to his Indonesian citizen. The purpose of this paper isto assess the position of the nominee agreement in Indonesia's legal system and the legal consequences arising in terms of the draft Civil Code and the Law on Agrarian. Agreement is an agreement unnamed nominee made based on the principle of freedom of contract and good faith of the parties. However, it should be noted that the law prohibits foreigners make agreements / related statement stock wealth / property (land) for and on behalf of others, sehingga the legal consequences of the agreement is the nominee of the agreement is not legally enforceable because the agreement was made on a false causa.Keywords: Nominee Agreement; Property Rights; Foreigners.